Frontier Large Language Models in Mathematical Reasoning and Scientific Knowledge Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 5 peer-reviewed papers addressing the following research question: Comprehensive comparison of frontier large language models on mathematical reasoning code generation and scientific knowledge v10. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.8/10. This report is a machine-generated literature synthesis and does not constitute or
Machine-generated literature synthesis.